Performance Analysis of Alternate Repeaters for On-Chip Interconnections in Nanometer Technologies. (2015) - Rajendar, S.; Chandrasekhar, P.; Rani, M. Asha; Naresh, R.
Abstract: As the geometries of integrated circuits continue to shrink into the deep nanometer regime, the impact of on-chip interconnects is dominant on the overall system performance. This paper explores the power-delay trade-off in alternate repeater insertion techniques. The repeaters are placed along global on-chip interconnects to compensate the loss in the wires and to regenerate the signal strength. All the repeater insertion techniques with 3-pi RC distributed interconnect model are implemented at 45 nm and 180 nm technology with supply voltage operated at 1 GHz. The performance metrics considered to compare the alternate repeated interconnects are power dissipation, propagation delay and power-delay-product (PDP).